Characterization of Nipa Palm’s (Nypa fruticans Wurmb.) Sap and Syrup as Functional Food Ingredients - Phetrit, Renuka; Chaijan, Manat; Sorapukdee, Supaluk; Panpipat, Worawan (My University, 2020)
Nipa palm (Nypa fruticans Wurmb.) sap and its syrup locally produced in southern, Thailand, were characterized. Sugar was the predominant dry matter of both sap and syrup (p < 0.05). Sucrose, glucose and fructose were detected in both samples. In both samples, potassium was the most abundant macroelement (p < 0.05), followed by sodium, phosphorus, magnesium and calcium, respectively. Iron, copper, zinc, manganese and iodine were also found. Syrup had higher total soluble solid, lower aw and pH, darker color with higher intermediate browning product (A285) and browning intensity (A420) than sap. Syrup had lower total phenolic and flavonoid contents than sap (p < 0.05). Vanillic acid was predominant in sap, whereas vanillic acid, rutin and trans-ferullic acid were identified in syrup. DPPH·-scavenging and ferrous ion-chelating abilities of sap were higher than syrup, whereas the ferric reducing antioxidant power of the syrup was higher (p < 0.05). Sap and syrup were able to inhibit α-glucosidase with the IC50 of 15.79 and 222.51 mg/mL, respectively. Similar FTIR spectra with the different intensities of sap and syrup were noticeable suggesting the identical compositions of both samples with different contents. The peaks at 3380 and 2924 cm−1 suggested the presence of carbohydrates and the bands at 1500–800 cm−1 represented the zone of the three major sugar including sucrose, fructose and glucose. Our result suggests that nipa palm sap and syrup can be used as potential sources of functional food ingredients.
Keywords: Characterization; Functional ingredient; Nipa palm; Nypa fruticans; Sap; Syrup